Young Tender Coconut Punching and Splitting Machine - Saraswathy Vellaitham; Muhammad Nabil Rosman; N. Farahaina Mustafa Sharaffuddin; Sidek, Noor Azizah; A. Nawawi (Multidisciplinary Applied Research and Innovation, 2023)
Demand for coconut in today’s market is increasing due to its high nutrient level and refreshing character. Therefore, coconut production and coconut selling among vendors also expanded in Malaysia. However, based on the studies and observation, we realize that coconut drink vendors still use machetes to get coconut water and also to cut them. Using traditional methods to cut the young tender coconut leads to injuries, it requires skills, more force and manpower. The purpose of this initiative is to develop a design for a machine which can decrease the likelihood of hazards while chopping coconuts with manual-based operation. This machine operates in manual, user-friendly, capable of punching and splitting the tender coconut. The machine’s development process involves design of the machine using SolidWorks, material selection, fabrication includes adhesive bonding, welding and testing to evaluate the efficiency of the product. The performance analysis demonstrated that the Young Tender Coconut Punching and Splitting machine provides safe, hygienic and less force or less movement cutting operation compared to traditional methods.